Aplikasi Game Edukasi Ilmu Pengetahuan Alam - Febri Haswan, Nofri Wandi Al-Hafiz (RJOCS (Riau Journal of Computer Science), 2017)
Lesson natural science with the discussion of the transportation system and the respiratory system, excretory system, the sense of hearing and sonar systems, light and optical instruments, the solar system and life on Earth, is to see and understand in textbooks alone (LKS), books used is the book Natural Sciences Curriculum 2013. the problem that often arises is the textbook used easily torn or are not durable and lack of interest in learning the studentsindependently and prices of books are more expensive. To overcome these problems, SMPN 4 Teluk Kuantan require a breakthrough in the process of learning to use the